Charge-Discharge Property of Non-Stoichiometric Lithium Iron Silicate. (25th October 2017) - Matsui, Ryoji; Katayama, Misaki; Inada, Yasuhiro; Orikasa, Yuki
Abstract : Lithium iron silicate, Li2 FeSiO4 exhibits a high theoretical capacity; however, the reversible charge-discharge reaction is proceeded actually only between the divalent and the trivalent of iron, and the excess lithium ion is not involved. In this study, we attempted to maximize the amount of iron redox couple by synthesizing non-stoichiometric compound compounds. In the highly non-stoichiometric composition, the charge-discharge capacity decreased due to the impurity phase was observed, but in the case of a small amount of lithium deficient composition the capacity increase and the improvement of rate capability were observed.